Integrating Software Metrics for Fortran Legacy into an IDE - Méndez, Mariano (2014)
Software Metrics have being used since the 70s, their purpose is to measure different software attributes, such as complexity and maintainability, to name a few. Software Metrics help programmers obtain valuable information about programs. That information is essential when working with legacy systems. Scientists have been producing Fortran programs for the last six decades, and some of those programs became legacy years ago.We have implemented a set of well known software metrics for Fortran into a widely used IDE (Integrated Development Environment) by means of AST (Abstract Syntax Tree). This integration allows developers to obtain software metrics from their source code while they are programming.